Nature tourism as a driver of sustainable development in the province of Pamplona, ​​Norte de Santander - Ortiz Flórez, Jazmín Solange; Cancino, Susan Elsa; Montañez Romero, José Clemente; Gualdrón Guerrero, Carlos Andrés; Cancino Escalante, Giovanni Orlando; Villamizar Quiñonez, César (Sello Editorial Unipamplona, 2025)
The book Turismo de Naturaleza is an academic work produced by an interdisciplinary group of professors and researchers from the University of Pamplona. This work analyzes the impact of sustainable tourism in the province of Pamplona, with a special focus on Pamplona as the municipal center and Santo Domingo de Silos as a particular case within the region. Through a multidisciplinary approach, the book proposes strategies to utilize nature tourism as a tool for economic, social, and environmental development. It is structured into five chapters. The first chapter establishes a conceptual foundation by conducting a bibliographic review that outlines the main definitions and classifications of tourism, providing a theoretical framework for subsequent analysis. The second chapter examines theories of economic development from a historical and conceptual perspective to understand their relationship with tourism as a catalyst for economic, social, and environmental dynamics in specific regions. The third chapter explores the functioning of the tourism cluster in the municipality of Pamplona, analyzing the interaction among the actors involved and evaluating their impact on regional economic development. The fourth chapter takes a strategic approach, identifying specific opportunities offered by nature tourism and proposing guidelines that integrate social and economic policies. This analysis highlights tourism’s role as a driver of local development, focusing on the sustainable management of tourist, natural, and human resources. Lastly, the fifth chapter presents a proposal for tourism development in the municipality of Santo Domingo de Silos, exemplifying the application of the proposed guidelines in a specific context.